Quantifying the decrement in utility from perceived side effects of combination antiretroviral therapies in patients with HIV. - Braithwaite, R Scott; Goulet, Joseph; Kudel, Ian; Tsevat, Joel; Justice, Amy C (Value in health : the journal of the International Society for Pharmacoeconomics and Outcomes Research, 2008)
The decrement in utility attributable to side effects from combination antiretroviral therapy (CART) is unknown and likely to influence clinical decisions regarding CART initiation and cost-effectiveness.
Keywords: Adult; Aged; Anti-HIV Agents; CD4 Lymphocyte Count; Confidence Intervals; Cost-Benefit Analysis; Drug Therapy, Combination; Female; HIV Infections; Humans; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Quality of Life; United States; Veterans